Maternal plasma angiotensin 1-7 concentration is related to twin pregnancy chorionicity in the third trimester of pregnancy - Pietruski, Paweł; Kosińska-Kaczyńska, Katarzyna; Osińska, Agnieszka; Zgliczyńska, Magdalena; Żebrowska, Kinga; Popko, Katarzyna; Stelmaszczyk-Emmel, Anna (Frontiers in Endocrinology, 2024)
Introduction Twin gestation is related to a higher risk of hypertensive disorders in pregnancy with possible risk stratification depending on chorionicity. It may be related to differences in plasma renin-angiotensin-aldosterone components between monochorionic and dichorionic twin pregnancies. The study aimed to analyze the plasma ANG II and ANG 1-7 concentrations in women with monochorionic and dichorionic twin gestation. Methods A prospective observational study included 79 women between 32 and 34 weeks of gestation with twin pregnancy (31 with monochorionic gestation and 48 with dichorionic gestation). Angiotensin II and angiotensin 1-7 concentrations were measured in the collected blood samples. Results No significant differences were observed in angiotensin II concentrations between the dichorionic and monochorionic group with significantly higher levels of angiotensin 1-7 being observed in the dichorionic group. Angiotensin 1-7 level was higher than angiotensin II in 20 women (64.5%) in the monochorionic group and in 42 women (87.5%, p=0.01) in the dichorionic group. Higher plasma concentrations of angiotensin II and lower concentrations of angiotensin 1-7 were found in 5 women with gestational hypertension and in 3 with preeclampsia compared to normotensive women. Discussion It is the first study investigating angiotensin II and angiotensin 1-7 in twin pregnancies regarding chorionicity. Our results showed that plasma angiotensin 1-7 concentration was related to chorionicity, while plasma angiotensin II level was not. In most women with twin gestation angiotensin 1-7 concentration exceeded the concentration of angiotensin II. A switch in the relation between angiotensin II and angiotensin 1-7 was observed in hypertensive pregnant women.